Calcarisporium yuanyangense sp. nov. (Calcarisporiaceae, Hypocreales), a fungal pathogen isolated from Ophiocordyceps nutans - Zhu, Juye; Tang, Dexiang; Liu, Zuoheng; Luo, Lijun; Yu, Hong (Phytotaxa, 2023)
In this study, a new species, Calcarisporium yuanyangense, was isolated from Ophiocordyceps nutans collected from Yuanyang County, Yunnan Province, China, and described by morphology and molecular phylogeny. Based on the combined dataset of five genes including the internal transcribed spacer gene region (ITS), the nuclear ribosomal small and large subunit gene regions (nrSSU and nrLSU), the gene encoding translation elongation factor 1-α (tef-1α), and the RNA polymerase II second largest subunit gene region (rpb2), phylogenetic analyses were performed by the maximum likelihood (ML) and the Bayesian inference (BI) methods to determine the phylogenetic position of C. yuanyangense in Calcarisporium. This species was clustered with C. cordycipiticola, C. xylariicola, and C. arbuscula to form a separate branch. Calcarisporium yuanyangense had the basic morphological characteristics of Calcarisporium, but still differed morphologically from the other species in the genus. This species was similar to C. arbuscula in conidia shape, but the conidia of C. yuanyangense were larger and had a higher length/width ratio than those of C. arbuscula. This study deepens the understanding of the host diversity and the distribution of this taxonomic unit, as well as provides important taxonomic data for further exploration of the genus Calcarisporium.